1986
DOI: 10.1037/0003-066x.41.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Unethical intimacy: A survey of sexual contact and advances between psychology educators and female graduate students.

Abstract: This report is based on a thesis by the first author for the Master of Arts degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
166
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(178 citation statements)
references
References 7 publications
10
166
2
Order By: Relevance
“…For any disadvantaged group member, assertive confrontation risks confirming stereotypes that the group is "difficult," "aggressive," or "oversensitive" in intergroup relations; however, for women, these labels not only signify intergroup tension-they also serve as warnings that women are violating gender role prescriptions (Barrett & Swim, 1998;Feagin & Sikes, 1994;Jones et al, 1984;Latting, 1993;Stephan & Stephan, 1985). Women may have concerns that assertive responding will cause disruption (Gutek & Koss, 1993), at the "the cost of the interaction" altogether (Goffman, 1959, p. 39), or even incite perpetrators to further escalate their offending behavior (Coles, 1986;Glaser & Thorpe, 1986;Goffman, 1959;Kowalski, 1996;Lorber, 1975;Loy & Stewart, 1984;Taylor, 1979). Furthermore, research across a variety of domains suggests that women may be less likely than men to be confident, to engage in risk taking, or to feel efficacious (Cohen & Swim, 1995;Jianakoplos & Bernasek, 1994;Johnson & Powell, 1994;Lundeberg, Fox, & Puncochar,1994;Streitmatter, 1997), especially if they have any doubts about their perceptions of ambiguous situations (Barrett & Swim, 1998;Crocker, Major, & Steele, 1998).…”
mentioning
confidence: 93%
“…For any disadvantaged group member, assertive confrontation risks confirming stereotypes that the group is "difficult," "aggressive," or "oversensitive" in intergroup relations; however, for women, these labels not only signify intergroup tension-they also serve as warnings that women are violating gender role prescriptions (Barrett & Swim, 1998;Feagin & Sikes, 1994;Jones et al, 1984;Latting, 1993;Stephan & Stephan, 1985). Women may have concerns that assertive responding will cause disruption (Gutek & Koss, 1993), at the "the cost of the interaction" altogether (Goffman, 1959, p. 39), or even incite perpetrators to further escalate their offending behavior (Coles, 1986;Glaser & Thorpe, 1986;Goffman, 1959;Kowalski, 1996;Lorber, 1975;Loy & Stewart, 1984;Taylor, 1979). Furthermore, research across a variety of domains suggests that women may be less likely than men to be confident, to engage in risk taking, or to feel efficacious (Cohen & Swim, 1995;Jianakoplos & Bernasek, 1994;Johnson & Powell, 1994;Lundeberg, Fox, & Puncochar,1994;Streitmatter, 1997), especially if they have any doubts about their perceptions of ambiguous situations (Barrett & Swim, 1998;Crocker, Major, & Steele, 1998).…”
mentioning
confidence: 93%
“…Faculty-student dual relationships have been discussed in supervision literature (Glaser & Thorpe, 1986;Kolbert et al, 2002;Schwab & Neukrug, 1994;Sullivan & Ogloff, 1998). Student supervisees have limited autonomy to give informed consent in the relationship, as supervision is a required component of counselor education programs (Bowman & Hatley, 1995;Sullivan & Ogloff, 1998).…”
Section: Types Of Multiple Relationships Between Faculty and Studentsmentioning
confidence: 99%
“…Sexual behaviors also occur between academic lecturers or clinical supervisors and their students. Glaser and Thorpe (1986) found, for example, that 31% of female psychologist respondents reported having experienced sexual advances by teachers or supervisors during their training. Although Skeen (1981) reported that in the case of academic affairs, "virtually all" of the liaisons were based on respect and friendship, the unequal power distribution between students and teachers suggests an ethical dilemma.…”
Section: The Broader Sociological Contextmentioning
confidence: 94%